French erudités and the construction of Merovingian history - Starostin, Dmitri; Kuleshova, Elena (História da Historiografia: International Journal of Theory and History of Historiography, 2016)
This article addresses the ways in which scholars of history who worked in France in the 16th century attempted to describe and consider early medieval history and how in the course of this process they made slight adaptations to the image of the early medieval Frankish history that corresponded to the needs of the educated community and the emerging French monarchy. Thus, the article compares how the scholars Claude Fauchet, Bernards de Girarnd Sieur Du Haillan and others looked at the process of construction of the Frankish kingdom and how they addressed the relationship between the Mediterranean core of the Late Roman Empire and the diocese of Gaul which had long attracted the attention of the Franks, who became Roman soldiers and foederati. It is suggested that the bifurcation in historical knowledge took place in the 1570s in the works of Claude Fauchet and Bernard Du Haillan, one of which may still be ascribed to the earlier group of humanists who operated within the framework created by Leonardo Bruni and Flavio Biondo, whereas Bernard Du Haillan, on the other hand, sought to overcome the ideas and terms used by them and conceived of Frankish history in different terms. He emphasized the discontinuity between the Roman Empire and the Frankish Gaul, but at the same time sought to avoid the use of the discourse of national self-identification that permeated the works of earlier humanists.